Association between Depression Prevalence and Adverse Childhood Experiences in Middle-aged and Older People - LU Weiwei, ZHU Rui, CHEN Jun, FU Tengfei, ZHANG Jian, LIN Yuejun (Zhongguo quanke yixue, 2022)
BackgroundDepression prevalence and adverse childhood experiences (ACEs) in middle-aged and older people has become an increasingly concerned issue, yet it in Chinese population has been less reported, and needs to be further explored.ObjectiveTo investigate the epidemiology of ACEs among middle-aged and elderly Chinese people, and to analyze its association with depression prevalence, providing an accurate delineation of ACEs and depression prevalence in this group of Chinese people.MethodsInformation of 7 035 middle-aged and elderly people≥ 45 years old who met the research requirements were selected during July to August, 2021 from the database of China Health and Retirement Longitudinal Study held by Institute of Social Science Survey, Peking University, in which the questions in the Center for Epidemiologic Studies Depression Scale used in the CHARLS, ACEs (including abuse, neglect, dysfunctional family) and individual characteristics were screened and generated into new dummy variables with the weight reassigned. Covariates of those with ACEs (treatment group) and those without (control group) were included in a propensity score matching model, and propensity scores of them were estimated using robust standard errors in multivariate Logistic regression, then the covariates of two groups were matched using the 1∶1 nearest neighbor matching, and were checked using balance diagnostics and common support assumption. The influence of ACEs on the depression in those with ACEs was quantified by the average treatment effect on the treated.ResultsOf the 7 035 respondents, 6 529 (92.81%) had experienced ACEs, 1 802 (25.61%) had experienced at least four ACEs, and 1 003 (14.26%) had a depressive state. Multivariate Logistic regression model demonstrated that age, gender, and self-rated health status were significantly associated with ACEs (P<0.05) . Individual characteristics of both groups after propensity score matching were comparable (P>0.05) , and went through the check of balance diagnostics and common support assumption. Propensity score matching-based analysis revealed that the risk of depression prevalence in those with ACEs was increased by a factor of 6.9% compared with those without (P<0.001) .ConclusionThe prevalence of ACEs among middle-aged and elderly Chinese people was higher, which may significantly increase the risk of depression prevalence. Therefore, it is urgently needed to establish a system of ACEs screening and intervening to improve the level of healthcare services and well-being for these people.